Physical Vapor Deposition of Cathode Materials for All Solid-State Li Ion Batteries: A Review - Uzakbaiuly, Berik; Mukanova, Aliya; Zhang, Yongguang; Bakenov, Zhumabay (Frontiers in Energy Research, 2021)
With the development of smart electronics, a wide range of techniques have been considered for efficient co-integration of micro devices and micro energy sources. Physical vapor deposition (PVD) by means of thermal evaporation, magnetron sputtering, ion-beam deposition, pulsed laser deposition, etc., is among the most promising techniques for such purposes. Layer-by-layer deposition of all solid-state thin-film batteries via PVD has led to many publications in the last two decades. In these batteries, active materials are homogeneous and usually binder free, which makes them more promising in terms of energy density than those prepared by the traditional powder slurry technique. This review provides a summary of the preparation of cathode materials by PVD for all solid-state thin-film batteries. Cathodes based on intercalation and conversion reaction, as well as properties of thin-film electrode–electrolyte interface, are discussed.